Utilizing a Physician Scribe in a Pediatric Plastic Surgical Practice: A Time-driven Activity-based Costing Study. Issue 10 (October 2019) - Cho, Jonathan; Sanchez, Karl; Ganor, Oren; Afshar, Salim; Ruditsky, Alex; Bierman, Alex; Taghinia, Amir H.
Abstract : Background: To use time-driven activity-based costing methodology to compare the costs of routine pediatric plastic surgical patient visits with and without a physician scribe. Methods: Pediatric plastic surgical clinic visits at a tertiary care facility with the following diagnoses were studied: skin lacerations, skin lesions, and plagiocephaly. Two plastic surgeons saw patients individually either with or without a scribe over a 10-month period. The time that the scribe and physician spent on the patient was recorded, including the duration of the clinic visit and time spent creating, dictating, reviewing, and signing the note. An average appointment activity time for each measurement component was produced, and a capacity cost rate was introduced to derive the cost per minute for a scribe and physician. Sensitivity analysis and paired t -test were conducted to analyze the results. Results: A total of 45 cases with a physician scribe were observed with an average appointment activity time of 12.83 minutes (4.97 min for the scribe, 0.92 min for the physician, and 6.95 min combined). A total of 72 cases without a physician scribe were observed with an average appointment activity time of 12.01 minutes. The total attributable cost saving per appointment was $13.82 when a physician scribe was utilized. Conclusion: Time-driven activity-based costing methodology showed that the use of a physician scribe reduced cost per office visit by substituting physician time for a less expensive resource.